Politics and Theatre in Twentieth-Century Europe - Morgan, M. author. aut Link
X, 212 p.
Keywords: This book explores the connection between politics and theatre by looking at the works and lives of Shaw, Brecht, Sartre, and Ionesco, providing a cultural history detailing the changing role of political theatre in twentieth-century Europe.